DESAIN MEDIA E-KOMIK INTERAKTIF FLIPBOOK MATERI UNGGAH-UNGGUH BASA SISWA KELAS VIII SMP LABSCHOOL UNESA 1 - Zakiah Inggrid Novianti; Octo Dendy Andriyanto (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to describe the design of an interactive e-comic based on a flipbook for eighth-grade junior high school students in labschool unesa 1. The method employed is Research and Development (R&D) using the ADDIE model, limited to the analysis and design stages. The results show that the designed media possesses multimodal, interactive, and contextual characteristics through the integration of text, illustrations, color, and layout. The comic serves as a medium for contextual application, supported by a krama dictionary and interactive features with exercises to enhance students’ motivation and comprehension. Thus, the media has the potential to improve students’ understanding and skills in appropriately applying unggah-ungguh basa.